Properties of silica porous glasses with the nanoparticle ensembles of some compounds - Lepikh, Y.I.; Doycho, I.K. (Physics and Chemistry of Solid State, 2023)
Properties porous silica glasses are systemized in this review. Also the methods of formation of the nanoparticles’ ensembles of the substances, which are useful for the microelectronics, are described. Porous silica glasses are perspective due to their chemically resistance, mechanical strength and development of their inner surface. Own electrical resistance is too big for the porous glasses’ specimens with standard sizes, that’s why ones use them as matrixes for luminescence type of sensors mainly. The luminescent properties’ dependence on the molecular structure of investigate substances (such as dyes and metal oxides), as well as on the nanoparticle ensemble technological formation condition is studied. It is revealed to which certain gases dyes of the specified type are sensitive and why it occurs in such manners. It is shown due to which of the described nano-size systems’ properties sensitivity is appeared. Besides, one can embed a conductive phase into the pores of glass due to features of its structure. After such treatment one can use the porous glasses as matrix for formation of resistance type sensors.